(3CSQGQ GdYQHjIs - (3YHO GdQMef Hf eMeO Hf YHjO Gddg GdCfUGQj , GHf GdCfHGQj, ceGd GdOjf CHh GdHQcGJ,J (B577 (3g` s ((3NGfbGg bLGSdMOGQ ` GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg cGTa GdZWGA heGfM GdYWGA Pi GdLhO hGdEHOGA hHYO abO PcQJ ai gPG GdcJGH GdehShe HCSQGQ GdYQHjI cKjQkG ef ePGgH GdfMhjjf HGH Yde eG Gdcde s
(3BNQgG (B:s
(3hdG HO ajeG PcQfG Cf GdbGajI cPG ef Cf jchf eMehdkG Ydi bGajI GdCTYGQ ai GdeTghQ hEdG de jUM JSejI GdbGajI bGajI hUdi Gddg Ydi SjOfG eMeO hBdg hSde hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HBNQgG eSGFd efThQI ai GdfMhs
(3HgG fXGe GdJYbjHIs
(3fbdJ Yf fSNI fUQ Hf eMeO Hf GdeXaQ Hf CHj Gdafhf GdfMhi GdHZOGOi GdPi bQCgG Ydi GdeUfa s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdfMhs